(untitled) - Considine-Meara, Eileen (Hoboken, N.J., 2007)
At Home With Kate offers an inside look at Katherine Hepburn's life and home, from the vantage of Eileen Considine-Meara, daughter of Hepburn's live-in cook and housekeeper.
Keywords: Motion picture actors and actresses,Hoạt động điện ảnh; United States,Mỹ